Role of mitochondria in brain functions and related disorders - Monu Yadav; Mini Dahiya; Jyoti Dagar; Narender Singh; Nidhi Sharma; Nitin Rawat; Pratibha Dhakla; Neha Minocha; Anil Kumar (Open Exploration Publishing Inc., 2022)
Mitochondria are important organelles for high energy synthesis, reactive oxygen species balancing, antiapoptotic molecule production, membrane stability, intracellular calcium buffering, neuroplasticity and neurotransmission. Dysfunction in mitochondria is considered to be involved in the pathophysiology of mental problems. It has been observed that several drug types used to treat brain illnesses can harm mitochondria by altering the oxidative phosphorylation system and the gene expression of mitochondria-related proteins. In some studies, it has been observed that mitochondrial biogenesis shows a therapeutic effect in the management of mitochondrial disorders. Many therapeutic compounds are effective in the activation of mitochondrial biogenesis. The comorbidity of mental problems observed in those with mitochondrial dysfunction and the change in the efficacy of the cellular respiratory system have attracted researchers to understand the pathways and possible therapeutic strategies in neurological disorders. This article has attempted to understand the impact of mitochondrial function and mitochondrial dysfunction in the pathogenesis of brain disorders to develop potential therapeutic drugs.